Chronic Iliac Vein Occlusion and Painful Nonhealing Ulcer Induced by High Venous Pressures from an Arteriovenous Malformation - Daniel P. Link; Phillip J. Granchi (Case Reports in Radiology)
Chronic femoral vein compression (May-Thurner Syndrome) is a known rare cause of deep venous thrombosis. Subsequent angiogenesis and the development of arteriovenous malformation (AVM) in the setting of chronic venous thrombosis is by itself a rare and poorly understood phenomenon. We report a case in which elevated venous pressures resulting from such compression appear to have resulted in the development of a pelvic arteriovenous malformation, which was further complicated by chronic, nonhealing painful lower extremity ulcers, and the development of extensive subcutaneous venous collaterals. Following successful embolization of the pelvic AVM and ablation of veins under the ulcers with laser and sclerotherapy, the patient's ulcers healed and she became pain-free.